Determination of Excess Pore Pressure in Under Consolidating Soil by using CPTu - Ihut, Karolina Villa Delfia; Wijaya, Martin; Lim, Aswin; Satyanaga, Alfrendo; Aglia, Grisella; Syifanaya, Sharfina Faradiba; Sugianto, Andy (Makara Journal of Technology, 2025)
North Jakarta is predominantly composed of soft soil that is still undergoing consolidation. According to research by Raharjo et al. (2022), excess pore pressure is still present in the soils of Jakarta. The degree of consolidation and excess pore pressure values indicate that consolidation is not yet complete (Raharjo et al., 2022). In this study, the researchers developed two methods to determine excess pore pressure using field testing. The Stress History and Normalized Soil Engineering Properties (SHANSEP) model equation from Ladd and Foot (1974), as well as Finite Element Method (FEM) modeling using the PLAXIS program, were utilized to estimate the excess pore pressure in the soil. The results from the SHANSEP-based analysis were then compared with those from the FEM analysis using PLAXIS. The comparison showed that the excess pore pressure estimated using PLAXIS closely matched the values obtained from CPTu tests based on the SHANSEP model. Interpretation of parameters from the Cone Penetration Test with pore pressure measurement (CPTu) indicates that the soil at the project site is still consolidating and undergoing settlement. Similarly, the settlement results from the PLAXIS analysis support this conclusion.